CRISPR-cas systems based molecular diagnostic tool for infectious diseases and emerging 2019 novel coronavirus (COVID-19) pneumonia - Xiang, Xiaohong (J Drug Target, 2020)
Emerging infectious diseases, the persistent potential for destabilising pandemics, remain a global threat leading to excessive morbidity and mortality. The current outbreak of pneumonia caused by 2019 novel coronavirus (COVID-19) illustrated difficulties in lack of effective drugs for treatment. Accurate and rapid diagnostic tools are essential for early recognition and treatment of infectious diseases, allowing timely implementation of infection control, improved clinical care and other public health measures to stop the spread of the disease. CRISPR-Cas technology speed up the development of infectious disease diagnostics with high rapid and accurate. In this review, we summarise current advance regarding diverse CRISPR-Cas systems, including CRISPR-Cas9, CRISPR-Cas12 and CRISPR-Cas13, in the development of fast, accurate and portable diagnostic tests and highlight the potential of CRISPR-Cas13 in COVID-19 Pneumonia and other emerging infectious diseases diagnosis.